Bioactive peptides with antioxidant and antihypertensive properties, obtained from chachafruto seed flour (Erythrina edulis) (2022)
ABSTRACT: INTRODUCTION Hypertension is an important risk factor for atherosclerosis and therefore predisposes to coronary, cerebrovascular and renal diseases, (Mejías C et al., 2004; Torruco-Uco et al., 2009). Food-derived bioactive peptides have great potential for applications such as functional foods and nutraceuticals, for the prevention and treatment of hypertension. Antioxidant tests and in vitro ACE inhibition, as well as in vivo tests, showed that bioactive peptides can be an alternative in the prevention of metabolic diseases such as hypertension. Therefore, it is inferred that chachafruto (Erythrina edulis) could reach be considered as functional and its implementation would generate an impact on food security and also on the prevention of metabolic diseases such as high blood pressure. OBJETIVE Evaluate the antioxidant and antihypertensive activity of bioactive peptides obtained from chachafruto seed (Erythrina edulis) by enzymatic hydrolysis. MATERIALS AND METHODS The method described by Adler-Nissen, (1986) with some modifications (Pedroche et al., 2002; and Guerra et al., 2017) was used for the hydrolysis of the protein concentrate, using the enzymes Flavourzyme® (F) and Alcalase® (A), enzyme/substrate (E/S) ratio 5%. ABTS* inhibition activity. The methodology described by Kuskoski et al. (2004) was followed. DPPH* inhibition activity. The methodology described by Braca et al. (2002) was followed with slight modification. The ACE-inhibitory activity was measured by the method of Cushman and Cheung (1971) with slight modifications, as described in a previous publication (Muguerza et al., 2006). For the in vivo tests, Wistar rats of 9-11 weeks of age were used, weighing between 180-220 g, with groups n=6, Whites, physiological saline 20 mg/kg, negative control (L-Name) 20 mg /kg, Positive Control (Captopril) 5.0 mg/kg and the two concentrations of hydrolysates, low (75 mg/Kg) and high. (150mg/kg). CONCLUSION • Sequential hydrolysis improve the degree of hydrolysis and biological activities of hydrolyzates • Chachafruto seed proteins have great antioxidant and antihypertensive potential • The in vivo activity shows that bioactive peptides can be an alternative in the prevention of hypertension